Importance of Construction of Waste Processing Plant - Tamar Ninidze (Research Parks Publishers, 2024)
As the global population continues to grow, waste management has emerged as a critical environmental and public health challenge. In Georgia, inadequate waste management infrastructure exacerbates environmental degradation, necessitating the urgent development of modern waste processing facilities. This study addresses the gap in Georgia's waste management practices by assessing public perception of waste processing plants and evaluating the feasibility of their construction.Using a mixed-method approach, this research involved a survey of 120 respondents across various regions of Georgia, combined with a comprehensive literature review and site visits to existing landfills. The survey results reveal that 92.5% of respondents support the construction of waste processing plants, and 84.2% are willing to use products made from recycled materials. These findings indicate a strong public endorsement for sustainable waste management practices.The study also identifies demographic trends, with younger and more educated individuals showing greater support for waste processing initiatives. The findings suggest that there is a significant opportunity to advance Georgia's waste management system by leveraging public support and implementing modern processing facilities.The practical implications of this study are far-reaching, providing valuable insights for policymakers, city planners, and environmental agencies. The data underscores the need for immediate action to construct waste processing plants, which will not only reduce landfill dependency but also contribute to economic development and environmental sustainability. Future research should focus on the economic feasibility of various waste management methods and the long-term environmental impacts of waste processing facilities.